Patients with NASH and cryptogenic cirrhosis are less likely than those with hepatitis C to receive liver transplants - O’Leary, Jacqueline G. (Clin Gastroenterol Hepatol, 2011)
BACKGROUND & AIMS: Many patients with cryptogenic cirrhosis (CC) have other conditions associated with nonalcoholic steatohepatitis (NASH) that put them at risk for complications that preclude orthotopic liver transplantation (OLT). METHODS: We followed all patients with NASH and CC who were evaluated for OLT (n=218) at Baylor Regional Transplant Institute between March 2002 and May 2008. Data were compared with those from patients evaluated for OLT because of hepatitis C (HCV)-associated cirrhosis (n=646). RESULTS: Patients with NASH and CC were older, more likely to be female, had a higher body-mass index, and a greater prevalence of diabetes and hypertension, compared with patients with HCV-associated cirrhosis, but the two groups had similar MELD scores. NASH and CC in patients with MELD scores ≤15 were less likely to progress; these patients were less likely to receive OLT and more likely to die or be taken off the wait list because they were too sick, compared with patients with HCV-associated cirrhosis. The median progression rate among patients with NASH and CC was 1.3 MELD points/year vs. 3.2 MELD points/year for the HCV group (P=0.003). Among patients with MELD scores >15, there were no differences among groups in percentage that received transplants or rate of MELD score progression. Hepatocellular carcinoma occurred in 2.7% of patients with NASH and CC per year, compared with 4.7%/year among those with HCV-associated cirrhosis. CONCLUSIONS: Patients NASH and CC and low MELD score have slower disease progression than patients with HCV-associated cirrhosis and are less likely to receive OLT.